Preeclampsia as a risk factor of the cardiovascular complications development - Alicja Maria Ozga; Aleksandra Obuchowska; Justyna Wójcik; Arkadiusz Standyło; Karolina Obuchowska; Żaneta Kimber-Trojnar; Bożena Leszczyńska-Gorzelak (Kazimierz Wielki University, 2020)
Introduction: The term "preeclampsia" (PE) refers to a multisystem disorder occurring after 20 weeks of pregnancy; it includes a new onset of hypertension and proteinuria and affects from 2 to 8% of all pregnancies. Cardiovascular disease (CVD) is a group of pathologies, which present significant mortality rate all over the world. The literature implicates that both disorders are linked in a sense of further cardiovascular complications in women who had preeclamptic pregnancy. Purpose: Evaluation of the relationship between pre-eclampsia and the risk of future potential maternal cardiovascular complications and proposal of the possible causes of this association. Materials and methods: We performed the database research using Pubmed, Springer Link and ResearchGate and we made review and meta-analysis of relevant studies. We searched for studies analyzing the relationship between preeclampsia and future maternal cardiovascular risk. Results: Systematic reviews and cohort studies qualified for the purpose of this review showed the relationship between preeclampsia and future cardiovascular diseases in mothers. The possible explanations include endothelium dysfunction enduring after delivery and the co-existence of common risk factors for both diseases. Conclusions: Preeclampsia is a risk factor predisposing to cardiovascular diseases and may lead to cardiac complications later in life. The course of pregnancies is very important for the future maternal health. Key words: preeclampsia; pregnancy; hypertension; cardiovascular disease